Empirical research in teaching and learning : contributions from social psychology - Mashek, Debra J.; Hammer, Elizabeth Yost.; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2011)
"Empirical Research in Teaching and Learning: Contributions from Social Psychology draws upon the latest empirical research and empirical-based theories from social psychology to inform the scholarship of teaching and learning. Provides an accessible theoretical grounding in social psychological principles and addresses specific empirical evidence drawn from teaching and learning contexts Features concrete strategies for use in the classroom setting Includes contributions from experts in both social psychology and the scholarship of teaching and learning"--
"Social psychology has always offered interesting insights into the form and function of teaching and learning. Yet emerging research has shown that social psychology is now perfectly poised to play a much greater role in the future of higher education -- both in optimizing teaching and enhancing student learning. Drawing upon the very latest empirical research and empirical-based theories, Empirical Research in Teaching and Learning presents a series of practical strategies and concrete tools from the field of social psychology for enhancing teaching and learning. After providing an accessible theoretical grounding in social psychological principles, chapters reveal how this theoretical lens informs our understanding of teaching and learning, address specific empirical evidence drawn from teaching and learning contexts, and offer concrete strategies for translating this evidence "on the ground." This book represents an important and much-needed resource for all who are interested in enhancing teaching and learning in the higher education setting"--
Machine generated contents note: Preface (Debra Mashek & Elizabeth Yost Hammer). -- Chapter 1: How can social psychology galvanize teaching and learning? (Regan A.R. Gurung & Kathleen C. Burns). -- Chapter 2: A social look at student-instructor interactions (Janie H. Wilson, Karen Z. Naufel, & Amy A. Hackney). -- Chapter 3: Self-Construal, culture and diversity in higher education (Shelva Paulse Hurley & Eric Alexander Hurley). -- Chapter 4: Unintentional prejudice and social psychology's lessons for cross-racial teaching (Elliott D. Hammer). -- Chapter 5: Relationships that support student autonomy and engagement (Johnmarshall Reeve). -- Chapter 6: Achievement is an attitude: The importance of help seeking attitudes when predicting academic achievement (Jessica Clevering, Shelley DeFord, Tasia Yamamura & Debra Mashek). -- Chapter 7: Applying the science of learning to the art of teaching (Diane F. Halpern & Clayton L. Stephenson). -- Chapter 8: Which strategies best enhance teaching and learning in higher education? (John Hattie). -- Chapter 9: Understanding faculty reluctance to assess teaching and learning: A social psychological perspective (Dana S. Dunn, Maureen A. McCarthy, Suzanne C. Baker, Jane S. Halonen, Stacy Boyer). -- Chapter 10: Applying social psychology in the college classroom: Teachers and learners need (your) scholarship (Randolph A. Smith).
Includes bibliographical references and index.
Print version record.
Keywords: Social psychology -- Study and teaching; Social psychology -- Study and teaching; Electronic books